Introducing the International Guiding Statement on alternatives to solitary confinement - Stroppa, Rachele; Moss, Dana (Torture Journal, 2023)
Based on the reflections of a multidisciplinary group of experts, Physicians for Human Rights Israel and Antigone worked on the International Guiding Statement on Alternatives to Solitary Confinement, proposing global guidelines for reducing and finally overcoming the use of solitary confinement in prisons